Where Is Here? Literary Strivings of „Little Brother“ - Kleprlík, Michal (American & British Studies Annual, 2015)
Review of Chapters in Contemporary Canadian Literature by Jiří Flajšar, Pavlína Flajšarová, and Vladimíra Fonfárová (Olomouc: Univerzita Palackého v Olomouci, 2012)